PKM Pelatihan dan Pendampingan Guru SD IT Assalam Jeunib Bireuen dalam Pembuatan Modul Ajar Kurikulum Merdeka - Muhammad Rizal; Muslihin Muslihin; Wahyudi Wahyudi; Rahmi Rahmi; Novianti Novianti; Muhammad Reza; Rahima Rahima; Dhiaurrahmi Dhiaurrahmi (Al-Qalam Institute, 2022)
This article aims to discuss the development of teaching modules in the independent learning curriculum. Teaching modules are standard in the independent curriculum as a substitute for lesson plans. The independent curriculum teaching module is a substitute for lesson plans that are formatted and varied in nature which include learning material/content, learning methods, interpretation, and evaluation techniques which are arranged in a systematic and riveting manner to achieve the expected indicators of success. The teacher develops teaching modules before carrying out learning in the classroom. One of the functions of the teaching module is to reduce the teacher's burden in presenting content so that the teacher can have a lot of time to become a tutor and help students in the learning process.